Ozone photodissociation: isotopic and electronic branching ratios for symmetric and asymmetric isotopologues - Ndengué, Steve; Meyer, Hans-Dieter (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2012)
We present new calculations of the branching ratios between the various electronic and isotopic photodissociation channels of ozone. Special emphasis is placed on the isotopic/isotopologue differences because the contribution of the ozone photodissociation to the oxygen isotope and ozone isotopologue enrichments or fractionations is important for atmospheric applications. These branching ratios, which depend on photon energy, have been calculated with a full quantum mechanical wavepacket propagation approach: the multiconfiguration time-dependent Hartree (MCTDH) method. Five ozone isotopologues are considered: three symmetric, 16O3 (noted 666), 16O17O16O (676), and 16O18O16O (686); two asymmetric, 16O217O (noted 667) and 16O218O (668). The 668 and 667 asymmetric isotopologues can dissociate into either 66 + 8 or 68 + 6 for 668 and into 66 + 7 or 67 + 6 for 667. In the ranges of the Chappuis and Hartley bands, the dissociation is very fast and electronic and isotopic branching ratios are obtained from the wavepacket fluxes through complex absorbing potentials (CAPs) located perpendicular to the dissociation channels of the potential energy surfaces (PESs) of the A 1B1 (Chappuis) and B 31A′ (Hartley/Huggins) electronic states. In the range of the Huggins band the dissociation is much slower and the isotopic branching ratios of 667 and 668 asymmetric isotopologues, (e.g; 668 → 66 + 8 or 86 + 6) are obtained from the ratios of two partial absorption cross sections corresponding to the selective excitation of one or the other of the two isomers of Cs symmetry, which dissociate respectively into 66 + 8 and 86 + 6. We find that the photodissociation of the 668 asymmetric isotopologue favors the 68 + 6 channel with a propensity varying between 52% (Hartley) and 54% (Huggins) as a function of the photon energy. The electronic branching ratios to the singlet channel (O3 + hυ → O(1D) + O2(1Δ)) are all close to 90% above ≈32 000 cm-1. Below this energy, the singlet channel is energetically closed and only the triplet channel (O3 + hυ → O(3P) + O2(3Σ)) is open. These branching ratios are required to calculate the photolysis rates of each ozone isotopologue, which in turn contribute to the atomic oxygen and the ozone isotopic enrichments in the atmosphere.